2003
DOI: 10.1007/s00442-002-1165-4
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of hydraulic redistribution in three desert phreatophytes

Abstract: We measured sap flow in taproots, lateral roots and stems within a single individual in each of three co-occurring tree species in a Chihuahuan desert arroyo to assess the seasonality and magnitude of hydraulic redistribution. Nocturnal reverse flow (hydraulic redistribution) was detected in shallow lateral roots of Fraxinus velutina and Juglans major during periods when surface soils were dry. Reverse flow in the Fraxinus lateral root ranged from near zero to 120 g h(-1), and was inversely correlated with nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 28 publications
3
99
0
4
Order By: Relevance
“…Thus, the 'drying roots' were probably being rehydrated both from above-ground plant parts due to hydraulic redistribution and from deeper moist soil layers due to hydraulic lift, thereby neutralising the deuterium concentration to some extent. Hultine et al [41] found that the magnitude of hydraulic redistribution was greater in roots when night-time vapour pressure deficit was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the 'drying roots' were probably being rehydrated both from above-ground plant parts due to hydraulic redistribution and from deeper moist soil layers due to hydraulic lift, thereby neutralising the deuterium concentration to some extent. Hultine et al [41] found that the magnitude of hydraulic redistribution was greater in roots when night-time vapour pressure deficit was low.…”
Section: Discussionmentioning
confidence: 99%
“…Scholz et al [14] found that the rate of reverse flow was linearly related to soil-leaf water potential gradient, with the greatest reverse flow rates occurring when this potential gradient was at its most negative values. Hultine et al [15] reported greater magnitude of hydraulic redistribution in roots when night-time vapour pressure deficit was low. The onset and the magnitude of hydraulic redistribution is thought to be regulated by the development of water potential gradients within the plant parts, between the plant parts and soil, and the nocturnal demand for water by the plant [16].…”
Section: Introductionmentioning
confidence: 96%
“…Se procedió a la adaptación de la propuesta de la Ecuación 6.20 con base en el modelo conceptual de RibAV: para la modelación a escala diaria se asumió un valor 1 para S time desde la consideración de que "HLw" es un fenómeno que usualmente ocurre de noche (Amenu y Kumar, 2008;Caldwell y Richards, 1989;Caldwell et al, 1998;Dawson, 1993;Hultine et al, 2003); se tomó como parámetro de ecuación la duración de 10 horas al día que se ha reportado (Ryel et al, 2002).…”
Section: Ascenso Hidráulico Radicular "Hlw (T) "unclassified
“…En este sentido es de resaltar que el "HLw" simulado para la época seca es mayor que el correspondiente a la época de lluvias, lo que se explica en función de la demanda evaporativa en mención y de los potenciales mátricos del suelo característicos de períodos con ausencia de lluvia: en total, las tasas de ascenso hidráulico radicular simuladas con RibAV están entre 0.83 y 1.02 mm/día para RA y 0.69 y 1.29 mm/día para RF, durante el período de simulación de 2922 días. Estas cantidades se encuentran dentro del rango preliminar que citan algunos autores (Hultine et al, 2003;Ryel et al, 2002), aunque aún se están perfeccionando los métodos de estimación de este movimiento de agua.…”
Section: Análisis Del íNdice De Evapotranspiración "Et Index " Caractunclassified
See 1 more Smart Citation